1996
DOI: 10.2141/jpsa.33.89
|View full text |Cite
|
Sign up to set email alerts
|

Crowing Characteristics of Jungle Fowls, Japanese Native Breeds and White Leghorn Breed of Chicken.

Abstract: Crowing of Red, Grey, Green and Ceylon Jungle Fowls, 16 breeds of Japanese native chickens and White Leghorn breed was recorded on tape and analyzed by a sound spectrography for the level of pitch, the length of duration and the number of syllable. The pitch was the highest in Grey and Ceylon Jungle Fowls and the lowest in Koeyoshi. Red and Green Jungle Fowls and Chabo had a relatively hight pitch. Duration was the longest in Totenko and longer in Tomaru and Koeyoshi. The number of syllable was 3 to 5 in the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…While the trachea of domestic fowl is not inserted into the sternum, it is considered that the thoracic bones such as clavicle, coracoid, and anterior part of the sternum restrict the space for vocal organs. Totenko is valued for its long, low crowing (Kuwayama et al, 1996;Akishinonomiya and Komiya, 2009). To generate this attractive sound, Totenko has a large anterior air sac and long trachea.…”
Section: Characteristics Related To Attractiveness Of An Ornamental Fowlmentioning
confidence: 99%
“…While the trachea of domestic fowl is not inserted into the sternum, it is considered that the thoracic bones such as clavicle, coracoid, and anterior part of the sternum restrict the space for vocal organs. Totenko is valued for its long, low crowing (Kuwayama et al, 1996;Akishinonomiya and Komiya, 2009). To generate this attractive sound, Totenko has a large anterior air sac and long trachea.…”
Section: Characteristics Related To Attractiveness Of An Ornamental Fowlmentioning
confidence: 99%
“…Some studies showed that genetics is an important element for crowing duration. Different breeds of chickens produced different crowing duration (Kuwayama et al 1996). In Japanese long crowing chickens, genes control crowing traits (Komiyama et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“… Kuwayama et al (1996) studied the duration and the pitch of crowing and reported that Totenko, Shokoku, Onagadori and Oh-Shamo produce a low voice. In this study, we noticed that Totenko, Shokoku, Onagadori and Oh-Shamo possess a larger mandible than Chabo and Tosajidori ( Tables 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed characteristics such as larger orbits and a circular-like silhouette in the present study are estimated to be the functional morphological characteristics for acquiring caregiving in ornament-type fowls. The Morphological Characters of the Bill and Orbit among the Oh-Shamo, Onagadori, Shokoku and Totenko Kuwayama et al (1996) studied the duration and the pitch of crowing and reported that Totenko, Shokoku, Onagadori and Oh-Shamo produce a low voice. In this study, we noticed that Totenko, Shokoku, Onagadori and Oh-Shamo possess a larger mandible than Chabo and Tosajidori (Tables 3 and 4).…”
Section: The Motivation Of the Selection In Ornament-type Fowlsmentioning
confidence: 99%